Piety and Populism in the Victory Interpretation: Study of Millennial Hijrah in Padang City - Susilawati Susilawati; Try Bunga Firma (JIA (Jurnal Ilmu Agama), 2023)
This study aims to see how millennials understand the concept of hijrah. This study uses a type of field research (field research), with a qualitative approach. The research was conducted in the city of Padang. Respondents were taken using purposive random sampling techniques, and data collection techniques, by direct interview techniques and surveys via questionnaires. Data were analyzed using Milles and Hubberman analysis. This study found that the concept of hijrah among Millennials in Padang City is more oriented towards the practice of changing appearance (clothing) and a populist lifestyle, rather than oriented towards increasing religiosity and the substance of actual hijrah according to Islamic law. This meaning looks ambivalent when juxtaposed with the meaning of hijrah contained in the interpretation of the Qur'an an an and Tafsir by the Ministry of Religion of the Republic of Indonesia. As a result, migrating among millennials in Padang City seems to be used as legitimacy to accommodate spiritualism identity instantly which in the end can trigger radicalism. This research is expected to add insight into knowledge, especially in the science of Religious Studies and the Interpretation of the Qur'an and Interpretation